2008
DOI: 10.1016/j.jvs.2007.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Vein wall re-endothelialization after deep vein thrombosis is improved with low-molecular-weight heparin

Abstract: How the vein wall endothelium responds after deep vein thrombosis (DVT) has not been well documented owing to limited human specimens. This report shows that low-molecular-weight heparin accelerates or protects the endothelium and preserves medial smooth muscle cell integrity after DVT, but that this effect is limited to a relatively early time period. Although most DVT prophylaxis is pharmacologic (a heparin agent), use of nonpharmacologic measures is also common. The use of heparin prophylaxis, compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 43 publications
(42 reference statements)
3
38
1
Order By: Relevance
“…These data are congruent with other studies reporting that a smaller thrombus does not correlate with a favorable vein wall response. 13,17,32,33 Our results suggest that the beneficial effect of LMWH on the vein wall fibrotic response is independent of thrombus size but dependent on the presence of PAI-1.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…These data are congruent with other studies reporting that a smaller thrombus does not correlate with a favorable vein wall response. 13,17,32,33 Our results suggest that the beneficial effect of LMWH on the vein wall fibrotic response is independent of thrombus size but dependent on the presence of PAI-1.…”
Section: Discussionmentioning
confidence: 61%
“…Previous experiments have confirmed that LMWH treatment results in less collagenolysis, 20 decreased fibrotic response, 39 and improved endothelial recovery, 33 and thus increased collagen gene expression may represent normal or advantageous vein wall healing response. Intrathrombus IL-1β was decreased in animals treated with LMWH in our study, perhaps secondary to a diminished inflammatory response in the setting of a smaller thrombus size.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The cDNA obtained was amplified using TaqPolymerase (Promega, Madison, WI) in the Rotor-Gene quantitative real-time polymerase chain reaction system (Quiagen, Hilden, Germany). SYBR green intercalating dye was used to monitor levels of DNA amplification for each gene 18. Commercially available primers were purchased for the following genes of interest: B-Actin RefSeq# NM_001101.3, CRP RefSeq# NM_000567.2, IL-6 RefSeq# NM 000600.3, MMP9 RefSeq# NM_004994.2, MMP2 RefSeq# NM_004530.2, SELP, RefSeq# NM_003005.3, SELPLG RefSeq# NM_003006.3, TLR4 RefSeq# NM_138554.3, and TLR9 RefSeq# NM_017442.2.…”
Section: Methodsmentioning
confidence: 99%
“…24 This observation has been shown chronically as well, with impaired endothelial responses through day 14 after DVT in a rodent model. 25 The endothelium is critical for normal vessel homeostasis, primarily maintaining an anticoagulant state by nitric oxide release, thrombomodulin expression, and antithrombin binding sites. 26 …”
Section: Pathophysiology Of Pts: Clinical Observations and Experimentmentioning
confidence: 99%